2010
DOI: 10.1111/j.1445-5994.2009.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Use and abuse of faecal occult blood tests in an acute hospital inpatient setting

Abstract: The FOBT was applied in clinically inappropriate settings without consideration to confounding issues, and often led to inappropriate clinical decisions with considerable cost to hospital and patient. There is no place for FOBT in an acute hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 10 publications
4
39
1
Order By: Relevance
“…A study performed in a hospital setting in Australia also detailed gross misuse of gFOBT. 17 gFOBT were requested in clinically inappropriate situations without consideration of possible confounding factors, often leading to inappropriate clinical decisions and additional costs to the hospital and patient: it was concluded that gFOBT had no utility in an acute hospital setting. An accompanying editorial commented: 'The study shows how poor use of technology generates ant-like activity of limited benefit that drives the misallocation of resources, and leads to substandard non-evidencebased patient care'.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed in a hospital setting in Australia also detailed gross misuse of gFOBT. 17 gFOBT were requested in clinically inappropriate situations without consideration of possible confounding factors, often leading to inappropriate clinical decisions and additional costs to the hospital and patient: it was concluded that gFOBT had no utility in an acute hospital setting. An accompanying editorial commented: 'The study shows how poor use of technology generates ant-like activity of limited benefit that drives the misallocation of resources, and leads to substandard non-evidencebased patient care'.…”
Section: Introductionmentioning
confidence: 99%
“…have previously shown that faecal occult blood test (FOBT) is performed for inappropriate reasons in acute hospital settings in Australia. Such testing also affected patients’ management adversely, either by leading to inappropriate or delayed referral for endoscopic investigation …”
Section: Discussionmentioning
confidence: 99%
“…Frequent diarrhea can irritate the anal verge and cause minor bleeding from anal fissures or hemorrhoids. 3 Obviously, the diagnostic workup should focus on finding and eliminating the cause of diarrhea rather than embarking on an endoscopic search for a potential GI bleeding site.…”
Section: Unfocused Goals and Irrelevant Testsmentioning
confidence: 99%